Strategic support for transformative communication in a cross-cultural setting. (2017) - Ryback, David; Motschnig, Renate
The concept of cultural intelligence has been developed over two decades ago, following the popularisation of the concept of emotional intelligence, itself a branching of Howard Gardner's multiple intelligences. The global reach of social media has encouraged the recognition of cultural intelligence on more of us increasingly over time. The partisan split in the governments of many western nations has forced even more attention on the need to bridge such divides with greater cultural intelligence, transforming our communication when interacting with very diverse entities. The recent spate of 'lone wolf' terrorist attacks points to further need to bridge cultural gaps, here between such 'lone wolves' and their surrounding culture. Innovative solution models are offered to help resolve some of these challenges. These include outreach programs involving collaborative cross-cultural learning, such as paired individuals from different cultures serving as models, academic support for inclusion and learning, as well as creative modes of international workshops.